Management Policy Analysis Of Siberut Biosphere Reserve Mentawai Archepelago Distric West Sumatera Province - Sahadi Didi Ismanto; Ardinis Arbain; Helmi Helmi; Daimon Syukri (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2021)
This research executed in Siberut island which has been specified Unesco as Biosphere Reserve. The purpose of research was to identify the policy which has been specified in Siberut, knows implementation of management, knows perception and participation of public and knows interaction of the parties involving in management Biosphere Reserve. Method applied is Inventory and contents analysis of policy, Indepth Interview with cross check, Open interview with descriptive qualitative and Inventory and Stakeholder analysis. Republic of Indonesia Government doesn't support expansion of Siberut Biosphere Reserve for all island. There is understanding difference and exploiting of Biosphere Reserve according to the Government with MAB-UNESCO so do with perception there are difference between publics Siberut with the Government. Local public assumes that forest Siberut is custom forest which its the domination stays at custom public according to custom Arat Sabulungan, where its the exploiting and management is done based on custom, but the Government considers to be state forest. Implementation of Siberut Biosphere Reserve Pledge based on Indicator Implementation released by Unesco, 1996 till now still uncommitting for overall of area Biosphere Reserve, except to of Core area (Siberut National Park). Implementation at core area based on Indicator Implementation (Unesco, 1996) mostly has been executed, except for Indikator 5,6,8,9 and 16. Role and influence MAB and TNS in Siberut still be low for the reason need to be improved. Keyword: Cagar Biosfer Siberut, Siberut Biosphere Reserve.